Integration of building information modelling (BIM) with materials management in construction project - Fayed Mogalli, Ali Hussein (2017)
Construction industry in Malaysia still lags behind other industries in terms of implementation of information technology. Materials management needs adequate consideration in complex construction projects due to the involvement of several elements of project. Hence, late delivery of materials can lead to delay that gives negative impact to overall project plan especially in schedule. BIM is considered as an effective way to solve the problems in the construction project life cycle. Therefore, the objectives of this research were to identify the challenges of BIM integration with materials management and to study the potential of BIM integration with materials management in construction project. This research focuses on the integration of BIM with materials management in construction project at Kuala Lumpur with G7 contractors involved and consultants. The quantitative (questionnaire) approach was used to gain information from consultants and contractors (G7). There were 304 copies of questionnaires distributed to the targeted respondents and 93 of the response were collected which was 30.59 % of total respondent. The data were collected and analysed using Statistical Package for Social Science (SPSS) version 21.0. The findings showed that, most of respondents agreed that lack of awareness, unavailability of data formats, lack of introducing and lack of understanding of BIM as challenges of BIM integration with materials management in construction project. Similarly, most of respondents agreed that BIM can integrated for planning and scheduling, controlling and monitoring, supply chain and storage of materials management as potential of BIM integration with materials management in construction project. The research finding encouraged the consultants and contractors in Malaysian construction project should understand BIM, knowledge of BIM and awareness of BIM in order to integrate BIM with materials management in construction project.